2023
DOI: 10.1038/s41598-023-27998-2
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning and metabolic modelling assisted implementation of a novel process analytical technology in cell and gene therapy manufacturing

Abstract: Process analytical technology (PAT) has demonstrated huge potential to enable the development of improved biopharmaceutical manufacturing processes by ensuring the reliable provision of quality products. However, the complexities associated with the manufacture of advanced therapy medicinal products have resulted in a slow adoption of PAT tools into industrial bioprocessing operations, particularly in the manufacture of cell and gene therapy products. Here we describe the applicability of a novel refractometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Furthermore, through metabolic flux modelling, Williams et al uncovered how low-pH environments caused a significant metabolic shift in cells, redirecting cellular resources from growth towards managing environmental stress and adverse conditions. These insights underscore the capacity of PAT, not only in enhancing process efficiency, but also for enriching our understanding of the underlying biological mechanisms, thus contributing to a continuous improvement in quality control and process optimization in real time [31].…”
Section: Enhancing Hospital Facilities With New Technologiesmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, through metabolic flux modelling, Williams et al uncovered how low-pH environments caused a significant metabolic shift in cells, redirecting cellular resources from growth towards managing environmental stress and adverse conditions. These insights underscore the capacity of PAT, not only in enhancing process efficiency, but also for enriching our understanding of the underlying biological mechanisms, thus contributing to a continuous improvement in quality control and process optimization in real time [31].…”
Section: Enhancing Hospital Facilities With New Technologiesmentioning
confidence: 83%
“…The verification and validation methods enabled by PAT support can ensure quality control in real time. The research by Williams et al [31] exemplified the profound impact of PAT in biopharmaceutical manufacturing, particularly in the optimization of cell and gene therapy processes. Their study employed the Ranger system, a novel refractometry-based PAT, which demonstrated its efficacy in real-time monitoring of metabolic activity within HEK293T cell cultures during the production of lentiviral vectors.…”
Section: Enhancing Hospital Facilities With New Technologiesmentioning
confidence: 99%
“…The implementation of Process Analytical Technology (PAT) systems significantly enhances the efficiency and speed of drug production through continuous manufacturing. PAT tools enable realtime monitoring and control of critical process parameters, leading to improved product quality and reduced material wastage (McDermo , 2023;Williams et al, 2023;Xiong et al, 2023). By utilizing PAT systems, pharmaceutical companies can optimize bioprocessing operations, such as cell culture monitoring and metabolic activity assessment, resulting in increased productivity and process robustness (Kumari et al, 2023;Thakur et al, 2022).…”
Section: B Acceleration Of Drug Production Through Continuous Manufac...mentioning
confidence: 99%
“…The implementation of Process Analytical Technology (PAT) systems significantly enhances the efficiency and speed of drug production through continuous manufacturing. PAT tools enable realtime monitoring and control of critical process parameters, leading to improved product quality and reduced material wastage (McDermott, 2023;Williams et al, 2023;Xiong et al, 2023). By utilizing PAT systems, pharmaceutical companies can optimize bioprocessing operations, such as cell culture monitoring and metabolic activity assessment, resulting in increased productivity and process robustness (Kumari et al, 2023;Thakur et al, 2022).…”
Section: B Acceleration Of Drug Production Through Continuous Manufac...mentioning
confidence: 99%